Development of the Adherence to Healthy Behaviors Scale. (September 2021) - Huang, Chen-Hui; Natashia, Dhea; Lin, Tzu-Chia; Yen, Miaofen
Adherence to healthy behaviors is a protective factor in the disease progression of chronic kidney disease (CKD). Measuring adherence can lead to the recognition of unhealthy behaviors and the suggestion of programs to prevent poor health outcomes. An assessment measurement for patients with CKD not requiring dialysis was developed and psychometrically tested. A convenience sample ( n  = 330) of patients with CKD attending a nephrology clinic in southern Taiwan completed the 13-item Adherence to Healthy Behaviors Scale (AHBS). A principal axis factor analysis and a parallel analysis demonstrated a three-factor structure accounting for 47.16% of the total variance. Confirmatory factor analysis indicated a good model fit. The criterion-related validity was adequate ( r  = .51; p  < .000), with a Cronbach's alpha of .70; the test-retest reliability demonstrated good stability ( r  = .70; p  < .000). The AHBS is a valid, reliable instrument to assess adherence to healthy behaviors among patients with CKD.